Twofileness. A Functionalist Approach to Fictional Characters and Mental Files. - Terrone, Enrico (Erkenntnis, 2021)
This paper considers two issues raised by the claim that fictional characters are abstract artifacts. First, given that artifacts normally have functions, what is the function of a fictional character? Second, given that, in experiencing works of fictions, we usually treat fictional characters as concrete individuals, how can such a phenomenology fit with an ontology according to which fictional characters are abstract artifacts? I will indirectly address the second issue by directly addressing the first one. For this purpose, I will rely on the notion of a mental file. I will argue that the function of fictional characters is the generation of mental files of a special kind. I will show that our experience of fictional characters as concrete individuals depends on the kind of mental files that are generated by fictional characters as abstract artifacts. I will conclude that an appreciator of a work of fiction can open two files about a certain fictional character; one about the character as an individual in the fictional world, and the other about the character as an abstract artifact in the actual world. In this sense, our relation to a fictional character is characterized by a duality of files or 'twofileness'.